Evaluation of TS 825 Thermal Insulation Requirements in Buildings in Turkey in Terms of Solar Radiation - Bektas Ekici, Betul (Yildiz Technical Univ, Fac Architecture, 2015)
TS 825 Thermal Insulation Requirements in Buildings, the obligatory standard, is still in effect, and is used to calculate the heating energy requirements of buildings in Turkey. The total solar heat gain through windows is calculated using the solar radiation table given in Appendix-C of TS 825. Although Turkey is divided into four different degree day regions according to this standard, Appendix-C offers the same solar radiation data for all regions. This study aimed to investigate the appropriateness of the Appendix-C table for the different degree day regions. The hourly solar radiation on the vertical surfaces of a building envelope was calculated for 16 selected cities. Long-term sunshine duration data for each location were obtained from the Turkish State Meteorological Service. It is demonstrated that the solar radiation table given in Appendix-C of TS 825 is not appropriate for the four degree day regions. The calculated solar radiation values of the cities are considerably different from the table values, with the ratios varying between 3.03% and 69.15% for horizontal surfaces, 0.171% and 53.29% for south, 0.25% and 22.15% for north and 0.60% and 40.42% for east and west oriented surfaces.
Keywords: Orientation; solar heat gain; solar radiation; window; TS 825